Pengaruh Penggunaan Media Kartu Kata Bergambar terhadap Peningkatan Penguasaan Kosakata Siswa Tunarungu - Rani Nirwanawati; Mohammad Efendi; Usep Kustiawan (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2015)
Hearing impairment student has limited vocabulary mastery. It causes problems in their learning which make them difficult in understanding or comprehending teacher’s explanation. The objective of this study is to describe the student’s vocabulary mastery before and after using picture word card media and also to analyze the effect of the use of picture word card media on the student’s vocabulary mastery with hearing impairment in the fourth grade. This study is a Single Subject Research (SSR) with A-B-A design. The data collecting were spoken test, written test, observation, documentation, and then they were analyzed by descriptive-statistic analysis. The result of this study showed that the use of picture word card media gave effect toward the student’s vocabulary mastery with hearing impairment in the fourth grade.Siswa tunarungu seringkali sulit memahami materi pelajaran karena keterbatasan perbendaharaan kosakata yang dimiliki. Tujuan kegiatan penelitian yaitu untuk mendeskripsikan penguasaan kosakata siswa sebelum dan setelah penggunaan media kartu-kata bergambar, serta menganalisis pengaruh dari penggunaan media terhadap penguasaan kosakata siswa tunarungu kelas 4 SDLB. Penelitian ini menerapkan rancangan penelitian subjek tunggal (SSR), desain A-B-A. Data dikumpulkan menggunakan tes lisan, tes tulis, observasi, dokumentasi dan diolah menggunakan analisis statistik deskriptif. Hasil penelitian membuktikan ada pengaruh penggunaan media kartu kata bergambar terhadap penguasaan kosakata subjek.